Analysis of Public Perceptions of The Existence of Islamic Banking and Conventional Banking in The Tegal City Area - Alawiyah, Nafisatul; Adinugraha, Hendri Hermawan; Sulthoni, Muhammad (Faculty of Islamic Economics and Business, UIN Prof. K. H. Saifuddin Zuhri Purwokerto, 2024)
The existence of Islamic banking and conventional banks usually have a strategic way as an intermediary institution and provide services in the payment business, but the type of the two banks can affect the preferences of prospective customers to choose between the two banks. This research is a descriptive study with a qualitative approach conducted through observation, interviews, questionnaires, and documentation. The level of public knowledge about Islamic banks and conventional banks can be categorized into a level that is still considered sufficient, not too broad. In the selection of banking institutions, people choose conventional banks because most people do not know the existence of Islamic banks. People's perceptions of Islamic banks are different. This perception can affect how people behave in choosing a particular bank for the issue of funds they have either to save or make loans at Islamic banks.